2023
DOI: 10.23950/jcmk/13320
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation response index and systemic immune-inflammation index are associated with severity of acute pancreatitis

Abstract: <b>Aim: </b>Acute pancreatitis (AP) is a disease with inflammation, and patients present with severe acute upper abdominal pain in emergency departments. AP can result in higher mortality as its clinical severity increases. Therefore, in this study, we want to investigate the clinical utility of the systemic inflammation response index (SIRI) and systemic immune-inflammation index (SII) in showing the severity of AP.<br /> <b>Material and methods:</b> Among the patients admitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…At a cutoff point of 3.72, SIRI demonstrated predictive precision for SAP, with a sensitivity of 92.0% and specificity of 59.3%, yielding an AUC of 0.782. 14 Furthermore, a study by Yildiz et al 15 on 201 patients also found higher levels of SIRI in SAP patients (mean SIRI 11.19 AE 6.27 in SAP vs 3.12 AE 3.01 in nonsevere AP; P < 0.001). At a cutoff point of 4.83, SIRI exhibited strong predictive capability for SAP, with an AUC of 0.890, and sensitivity and specificity values of 83.8% and 80.0%, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…At a cutoff point of 3.72, SIRI demonstrated predictive precision for SAP, with a sensitivity of 92.0% and specificity of 59.3%, yielding an AUC of 0.782. 14 Furthermore, a study by Yildiz et al 15 on 201 patients also found higher levels of SIRI in SAP patients (mean SIRI 11.19 AE 6.27 in SAP vs 3.12 AE 3.01 in nonsevere AP; P < 0.001). At a cutoff point of 4.83, SIRI exhibited strong predictive capability for SAP, with an AUC of 0.890, and sensitivity and specificity values of 83.8% and 80.0%, respectively.…”
Section: Discussionmentioning
confidence: 88%